2018
DOI: 10.1007/s10792-018-0925-z
|View full text |Cite
|
Sign up to set email alerts
|

Ocular sebaceous gland carcinoma: an update of the literature

Abstract: Ocular SGC is an aggressive tumor associated with poor prognosis. Early identification and appropriate treatment may help improve the prognosis. New insight into its pathogenesis and the immunohistochemical profile may lead to the development of new effective treatment strategies, along with traditional therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 116 publications
2
43
1
Order By: Relevance
“…As previously reported [3], SGC generally occurs in older individuals, with those aged 46-75 years being in the highincidence group. ese results are consistent with those of another study that reported SGC of the eyelid arising in the sixth or seventh decade of life (57-72 years) [2]. However, SGC can also occur in older children and young adults [20].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…As previously reported [3], SGC generally occurs in older individuals, with those aged 46-75 years being in the highincidence group. ese results are consistent with those of another study that reported SGC of the eyelid arising in the sixth or seventh decade of life (57-72 years) [2]. However, SGC can also occur in older children and young adults [20].…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, females (52.3%) were more likely to be affected by the disease than males (the female : male ratio was 1 : 0.9), which is in agreement with another study that showed a female preponderance for SGC, with the female : male ratio at 1.4 : 1 [2]. In reality, though, there was no correlation between positive EBER staining and age and gender after Pearson's χ 2 and Fisher's exact tests were carried out.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Full-thickness eyelid tumor resection with posterior lamellar is the golden standard and superior to non posterior lamellar resection [25,26]. Mohs surgery has been recommended as treatment of sebaceous carcinoma with excellent results with 11% recurrence rate for primary tumours [27][28][29][30][31].…”
Section: Treatmentmentioning
confidence: 99%
“…2) [24] Treatment Primary treatment method Surgery with posterior lamellar resection. [25,26] Clinical margin At least 4-5 mm. 3) [6,10,13,[38][39][40][41][42][43] Method of surgery Multi-stage resection with delayed closure, frozen sections or Mohs surgery are recommended to verify tumour-free margins.…”
Section: Follow-upmentioning
confidence: 99%